Estresse social crônico e o sistema circadiano: efeitos no relógio central e oscilador hepático periférico - Ota, Simone Marie [UNIFESP] (2019)
We humans, as well as several living organisms, present biological rhythms of approximately 24 hours, such as the sleep-wake cycle, locomotor activity, temperature, and hormone secretion rhythms. The maintenance of these rhythms allows us to perform various activities in an optimal time of the day, taking advantage of the variation of light and temperature, among other environmental cycles. The 24-h light-dark cycle is caused by the Earth’s rotation and influences other environmental cycles, such as temperature, humidity, availability of food, among others. Therefore, it is conceivable that organisms have evolved a temporal system that allows them to carry out certain activities at the best time of the day, according to the variation of the environmental cycles. Several studies have shown that in mammals, this temporal system, also called the circadian (about a day) system, has a primary center in the brain that generates an internal rhythm of approximately 24 h, located in the suprachiasmatic nucleus (SCN). In addition, some other body tissues are also able to perform their functions, such as metabolism, with the same period as the rhythm produced by the SCN. This is because every cell appears to have a “molecular clock”, provided by the production of some proteins in a near 24-h cycle, the so-called “clock proteins”. Thus, some peripheral tissues, i.e., other than the SCN, are able to maintain the rhythm in cultures outside the body. However, the SCN produces a stronger and lasting rhythm, aligns its rhythm to the environment light-dark cycle and sends signals to synchronize the rhythms generated in other tissues. For that reason, it is also known as the central clock or oscillator. It is important that our circadian system is synchronized with the external environment, so that we can feed, sleep and wake up, work, among other activities, at optimal times. And when this does not happen, we can see the negative effects on attention, sleep, digestion. This is what happens when we travel to places with time zones different from ours or also with shiftworkers. Since it is important to keep our organism adjusted to external time, and the most important environmental clue for this to occur in mammals is the light-dark cycle, it is desirable that the central oscillator is not influenced by clues other than light or clues that cannot be predicted. With this knowledge in mind, we wondered if the SCN would be protected from stressful situations, which are often unpredictable and unavoidable in today’s society. For humans, social stress, especially when chronic, is one of the most severe kinds of stress and is related to the development of metabolic diseases and some psychiatric disorders, such as depression. However, in our life, it is difficult to establish a cause-andeffect relationship among stress, circadian rhythm disturbance and health consequences. For this reason, we used a social stress model in mice to assess the stress effects on the circadian activity rhythm, which is controlled by the SCN and easily evaluated. We proposed to answer the following questions: 1. Is chronic social stress capable of affecting the circadian 106 locomotory rhythm and maintenance of the rhythm in the central clock? 2. Is chronic social stress capable of affecting the temporal organization of the central oscillator and oscillation in a peripheral tissue? In Chapter 2, we reviewed some studies that investigated the effects of stress on circadian rhythms. Previous studies from our group have already shown that acute social stress reduces locomotor activity. However, the time when there is a sharp increase in activity and the duration (period) of the activity-rest cycle do not change. This evidence suggests that the SCN continues to maintain its rhythm and is not affected by social stress. Regarding the effects of chronic stress, the results of studies available in the literature are still contradictory. One of the reasons may be that the shape of the observed rhythms can be altered by several factors. For example, the body temperature rhythm may reflect, not only the rhythm expressed by the biological clock, but also be altered by some momentary physical activity or exposure to external heat or cold. Therefore, as discussed in the second chapter, several methodological precautions must be taken so that the observed rhythm is not masked by external or other internal factors. In Chapter 3, we investigated whether the rhythm of locomotor activity is affected by chronic social stress. For this experiment, we kept our animals in constant red light (which is almost imperceptible to rodents and would resemble constant darkness). To measure locomotor activity, we used activity wheels. Part of the animals were exposed to an aggressive mouse (for the social stress) a few minutes, for ten days, during the active time or during the inactive time, and their rhythms were compared to animals that were not exposed to stress. Interestingly, , the stressed mice showed reduced levels of activity, but the time of the sharp increase in activity and the period of the activity rhythm did not change, similar to that observed with acute social stress in rats. These results suggest that the SCN is not affected by chronic social stress either. In Chapter 4, we replicated the observations of the previous chapter regarding the effect of stress on the rhythm of locomotor activity. During the 10 days of social stress, the defeated animals showed lower activity levels, but the time of the sharp increase in activity and the period were not different from the non-stressed animals. In addition, we also analyzed the rhythm of expression of one clock protein in tissue cultures of SCN and liver. This analysis is important because it allows us to observe the effects of stress in these isolated areas. For this experiment, we used transgenic mice that produced this clock protein linked to a protein that produces bioluminescence, which permitted us to detect luminescence, and therefore, the rhythm of protein production. As expected, the rhythm of this clock protein production in the SCN was not different between the two groups. However, in the liver, the peak time of production of the clock protein was delayed in tissues from animals that had experienced social stress. These results support the idea that the central clock is protected against stress, but the peripheral clock in the liver is not. In Chapter 5, we investigated a possible mechanism by which stress could affect the Summary 107 clock in the liver, as observed in the experiment of the previous chapter. Our supposition was that corticosterone, a hormone that is released in greater amounts in response to stress, could be responsible for changing the rhythm of production of that clock protein in the liver. To investigate this hypothesis, we made liver and SCN tissue cultures of transgenic mice of the same type as in the previous chapter and added corticosterone in part of the cultures. The rhythm of production of the clock protein was not different in the treated from the untreated SCN cultures. On the contrary, the peak time of this protein production was delayed in liver cultures in which the hormone was added in medium concentrations. Again, the result supports the idea that the SCN is not affected by stress, but the peripheral clock in the liver is, and a possible mechanism is the increase of corticosterone in response to social stress. Considering the idea that desynchrony between the SCN- and the peripheral clock time, such as in the liver, may have consequences for mental health, we also performed behavioral tests after the social stress protocol in mice (Chapter 6). The tests were chosen with the aim to allow us to observe if the animals display depressive-type behaviors, i.e., those resembling what is observed in depressed patients. Although some research groups had already observed these effects after social stress, we did not find differences between stressed and non-stressed animals. Perhaps the age of the animals (adults, while other groups use adolescent animals) could explain this difference, since youngsters may be more vulnerable to the effects of stress. In addition, other methodological differences in the stress protocol and behavioral assessment might explain the different results we have obtained compared to other works. In Chapter 7, we discussed the results obtained, comparing them to other studies and their implications, in addition to suggesting future experiments. Regarding the effects of stress on the rhythm of locomotor activity, although one study observed a change in the time of peak activity, our results are in agreement with others, which did not observe changes in the rhythm. This disagreement may be related to methodological differences, such as keeping the animals in constant red light, whereas the other study, kept the animals under a light-dark cycle. Other studies have also showed that injection of corticosterone or a similar synthetic hormone also changed the peak of clock protein production, in the liver and other peripheral organs. Moreover, other hormones that are secreted in response to stress, such as adrenaline and noradrenaline, also appear to have the same effect. Therefore, we proposed a future study to block these hormones and evaluate if the effects of chronic social stress would still be the same. In addition, since other areas of the brain also appear to show rhythmic production of clock proteins, it would be interesting to study the effects of social stress in areas associated with emotional regulation, since desynchronization of biological rhythms seems to be associated with disorders such as depression. In conclusion, the central biological clock seems to be protected against the effects of chronic social stress, but the peripheral clock in the liver does not. The desynchronization between these clocks 108 and perhaps other peripheral clocks may be associated with health problems, such as the ones observed in shiftworkers.